Work In Progress : Improving Youth Labor Market Outcomes in Emerging Market and Developing Economies - Ahn, JaeBin (Staff Discussion Notes; Staff Discussion Notes, 2019)
Economic development and growth depend on a country's young people. With most of their working life ahead of them they make up about a third of the working-age population in the typical emerging market and developing economy. But the youth in these economies face a daunting labor market-about 20 percent of them are neither employed, in school, nor in training (the youth inactivity rate). This is double the share in the average advanced economy. Were nothing else to change, bringing youth inactivity in these economies down to what it is in advanced economies and getting those inactive young people into new jobs would have a striking effect. The working-age employment rate in the average emerging market and developing economy would rise more than 3 percentage points, and real output would get a 5 percent boost.